History and philosophy of sport and physical activity - Kretchmar, R. Scott (Robert Scott); Gleaves, John; Llewellyn, Matthew P.; Dyreson, Mark 1959- (Human Kinetics, 2017)
History and Philosophy of Sport and Physical Activity blends historical investigations and philosophical insights regarding sport and physical activity. This cross-disciplinary text shows how theory in the humanities can affect professional practice. The author team offers philosophical and ethical analyses alongside explorations of changes in culture. The text follows a chronology of human movement from our origins as hunter-foragers to the present. They blend their specific areas of expertise to present a thorough integration of philosophy and history, capitalizing on the strengths of both disciplines. History and Philosophy of Sport and Physical Activity is designed to reduce any gap that might exist between good ideas and sound professional behavior. Historical lessons and philosophical analyses are seamlessly integrated. Pedagogical aids and instructor ancillaries optimize the use of History and Philosophy of Sport and Physical Activity in the classroom, and the book's topical analysis will support professionals and researchers. Readers will understand the intersection of history, culture, ideals, ethics, and professional practice from sport's leading philosophers and historians